Strategi Manajemen Konflik Dalam Meningkatkan Kinerja Dosen Di Perguruan Tinggi - IBNATUR HUSNUL, NISAK RUWAH; Purnawati, Elisa; Dwi Septiningrum , Liana (Universitas Tidar, 2024)
This study aims to analyze effective conflict management strategies in improving the performance of lecturers in higher education. Workplace conflicts often affect productivity, teaching quality, and job satisfaction among lecturers. Using a descriptive qualitative approach, this research examines how strategies such as mediation, open communication, and collaboration can create a conducive working environment. Data were collected through in-depth interviews with lecturers and university leaders, as well as observations and document analysis. Data analysis was conducted using triangulation. The results show that effective conflict management strategies can improve lecturer productivity, enhance the quality of peer interactions, and foster workplace innovation. Well-managed conflicts not only reduce tension but also increase job satisfaction and motivation.